Improving transparency in data access processes: Developing best practice standards and promoting system-wide change through a competitive funding call - Yemi Macaulay; Ester Bellavia; Rachel Brophy; Angela Coulter; Ben Glampson; Bethany Gilbert; Alan Holcroft; Erik Mayer; Edel McNamara; Katherine O'Sullivan; Paola Quattroni; David Seymour; et al. (International Journal of Population Data Science)
Introduction Transparency in the use of data for research benefits the public and researchers by fostering trust and enabling efficient data sharing. Public support for access to their data for research depends on robust data security, the absence of conflicting interests, and a clear demonstration of public benefit, all of which must be evident through transparent practices. A lack of clarity in data access processes can delay research, highlighting the need for clear and streamlined approval procedures. To maintain what is often referred to as a `social license to operate', organisations must meet and uphold societal expectations, with transparency being a key dimension of that responsibility.